The Integration of Digital Literacy in EFL Classroom - Cahya, Astuti Dwi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
The purpose of this research is to find out the integration of digital literacy in the EFL classroom. The qualitative approach was employed in this study, which took place at SMPN 4 Magetan. Two participants were involved in the study, and data collection utilized two instruments: observation and interview. The collected data was analyzed through observation and interview techniques and steps. The research findings indicate that teachers at SMPN 4 Magetan exhibit competent classroom management skills in implementing digital literacy. They demonstrate the ability to effectively prepare learning materials and deliver clear explanations, particularly in teaching English as a foreign language (EFL). It is essential for EFL teachers to consider the elements of digital literacy. The result shows that the integration of digital literacy in EFL classes at SMPN 4 Magetan has not been fully implemented, with the teacher's role being crucial in supporting the findings observed in this study.